Social representations of sexual orientation and gender identity among nurses in Portugal - Gomes, A.; Saleiro, S.; Pegado, E.; Barroso, M. (Sexuality Research and Social Policy, 2023)
Introduction A number of studies in different countries have highlighted discrimination of sexual and gender minorities in healthcare environments. Although Portugal has made considerable progress in the acquisition of rights for LGBT people, there are still gaps in the training of health professionals. Among these, nurses are at the forefront of many of the close interactions with patients. This article aims to ascertain the social representations of sexual orientation and gender identity among nurses in Portugal from a sociological perspective. Methods A quantitative survey of Portuguese nurses was conducted in an online questionnaire. The data were collected between May and July 2020, and the participants were recruited through the Portuguese Nurses Association. The universe of the study consisted of 75,928 nurses, from which a sample of 899 was obtained. Results The results showed that Portuguese nurses tended to have a positive social attitude towards non-normative sexual orientations and gender identities, which they perceived as a natural expression of human diversity. This attitude was stronger among the younger, politically left-leaning participants without a religion, and close to LGBT people. The vast majority recognized that they lacked adequate training in LGBT issues and a significant part expressed the need to bridge that gap, mainly with regard to gender identity. Conclusions and Policy Implications This study provides insights into the insufficient inclusion of LGBT matters in nursing courses, and the need for ongoing, and specialized training. Knowledge and cultural competencies in the care of LGBT people should be guaranteed and made universal for nursing and other health professionals in order to reverse the reduction in their access to healthcare and ensure respect for the human right to health for LGBT people.